Ayureda In The Battle Against Covid 19 –A Global Pandemic - Savitha , P K; Kapoor, Ritu; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2020)
Coronavirus is a pandemic disease becoming a great disaster in the world.Covid -19 has evolved itself into a pandemic, affecting a large population irrespective of their physical features, dietary patterns, and physiological attributes. Ayurveda considered it as Janapada udwamsa vikara. Initially ,to china, patients are admitted to the hospital due to unknown causes of pneumonia and finally diagnosed as Corona virus disease. Immuno competent persons are having an only common cold as a symptom. People show the symptoms in a mild, moderate, and severe manner based on many associated factors. The main factor is the immunity that helps to prevent the clinical manifestation of the virus to great extent. In Ayurveda many drugs are having immunomodulatory, Antiviral, jwarahara action is mentioned, Also we get a comparison of symptoms of corona virus disease as Agantuja sannipata jwara lakshna. Hence, we have to explore more in the field of Ayurveda.